Analisis Kesalahan Siswa SMP dalam Menyelesaikan Soal TIMSS-like Domain Data dan Peluang - Anisha Dwi Rahmawati (Program Studi S1 Matematika UNESA, 2020)
Indonesia's position is relatively very low compared to other Southeast Asian countries participating in TIMSS. From the results of the TIMSS ranking of Indonesian students is low, it is known there are still many mistakes made by students. One effort to solve this problem is to find out where the location of errors that are often made by students and the factors causing students make these errors. In this study, the method used is a descriptive method that aims to describe the types and factors of student error in solving TIMSS-like domain Data and Chance problems. The subjects of this study were 3 out of 19 Lembaga Bimbingan Belajar (LBB) Primagama Sukodono students in class IX SMP selected based on the number of errors and variations in the types of errors made during the written test. The results showed that in solving TIMSS-like domain data and chance problems, students made errors in understanding the questions was22.1%, errors in transforming was 9.47% and errors in process skills was 4.21%. The reason students make these errors is students are not careful in reading the questions, do not understand the purpose of the question, wrong in choosing a solution and lack of practice questions. Keywords: error analysis, TIMSS-like data and chance problems.